Effect Modification by Attention Deficit Hyperactivity Disorder (ADHD) Symptoms on the Association of Psychosocial Work Environments With Psychological Distress and Work Engagement - Nagata, Masako; Nagata, Tomohisa; Inoue, Akiomi; Mori, Koji; Matsuda, Shinya (Frontiers in Psychiatry, 2019)
Objective The aim of this study was to examine whether there are differences in association between psychosocial work environment and psychological distress / work engagement among employees with and without attention-deficit hyperactivity disorder (ADHD). Methods A total of 2,693 employees at a pharmaceutical company were surveyed using a self-administered questionnaire evaluating ADHD tendency (Adult ADHD Self-Report Scale Screener), psychosocial work environment (Brief Job Stress Questionnaire), depressive symptoms (K6), and work engagement (Utrecht Work Engagement Scale). Results Job control (standardized partial regression coefficient β=-0.267) had a significant negative effects on psychological distress among ADHD employees, while job demands and social support had not. Among non-ADHD employees, all measured psychosocial work environment factors were significantly associated with psychological distress (job control: β=-0.167, job demands: β=0.147, and social support: β=-0.287). Significant interaction effects were observed between ADHD severity and both job control (β=-0.067) and social support (β=-0.052) on psychological distress. All psychosocial work environment factors were associated with work engagement in both groups, but the interaction effect was not observed between ADHD severity and each measured psychosocial work environment factor. Conclusions Job control was the only factor that was related to psychological distress among those suffering from ADHD symptoms, suggesting that control over work may be a key factor to prevent psychological distress among such population. This study also found no difference in the association between the psychosocial work environment and work engagement between the ADHD and non-ADHD group. To the best of our knowledge, this study was first to clarify the different association with psychosocial work environment on psychological distress between in employees with/without ADHD. These findings can aid employers how to arrange work environment for those suffering from ADHD-tendency.